Maintenance of Sheatfishes (Ompok hypopthalmus) Fingerling with the Addition of Probiotic Boster Biolacto to Feed with Different Doses in the Recirculation System - Risma Safitri; Usman M Tang; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research aims to determine the optimal Biolacto probiotic boster dose on feed mixing to improve feed efficiency, growth rate and survival of coriander (Ompok hypopthalmus) in recirculation systems. The research was conducted for 40 days from February to April 2019. This research was conducted at the laboratory f aquaculture technology Faculty of Fisheries and Marine Sciences, Riau University. The experiment method was done experimentally using a Completely Randomized Design (RAL) which consists of 5 treatments and 4 replications, is treatment 1). 0 mL/kg of feed (control); 2).3 mL/kg of feed; 3).5 mL/kg of feed; 4).7 mL/kg of feed; 5).9 mL/kg of feed. The results of this study showed the addition of probiotics Biolacto in the feed to give effect to the growth rate of daily seeds of sheatfishes, feed efficiency and feed conversion ratio. The addition of probiotics at 9 mL/kg of feed gave the highest yield on the daily growth rate of 1.89%, the highest yield on feed efficiency of 84.61% and the best feed conversion ratio of 1.18. However, survival was not significantly different between treatments.Keyword : Sheatfishes, Probiotic Boster Biolacto, Resirculation system